Effect Of Anabolic Steroids Consumption On C- Reactive Protein (CRP) In Bodybuilders - H Arazi; M Ebrahimi; K Hosseini (Tehran University of Medical Sciences, 2011)
Background and Aim: Prevalence of anabolic steroids (ASs) consumption among bodybuilders has increased progressively. Therefore, the purpose of this study was to evaluate the effect of ASs consumption on C-reactive protein (CRP) in bodybuilders. Materials and Methods: Sixty healthy men (age: 24/1± 9/1yr weight: 77±10 kg and height: 172±12 cm) participated in the study voluntarily. These subjects were selected from three groups. First group (FG) was bodybuilders who consumed ASs (n=20), second group (SG) was bodybuilders who did not consume ASs (n=20) and third group (TG) were untrained subjects as control (n=20). Blood samples were collected in fasting state (12 hours) at 09:00 for CRP assessment. Strength and volume of the forearm, pectoral major and femur muscles were measured via 1RM test and muscle circumstances, respectively. Speed was assessed by 30m speed test. Analysis of variance test and LSD post-hoc test was used. Results: FG had significantly greater blood CRP (P<0/05) compared to other groups. However, differences between SG and TG were not significant. Muscle strength, and forearm and femur circumstances were greater in FG than other groups. Furthermore, this was greater in SG than TG. But chest circumstance was greater in FG and SG than TG only. There were no significant differences in speed between groups. Conclusion: ASs consumption for muscle strength and volume improvement in bodybuilders is accompanied by higher level of CRP (as a cardiovascular risk factor).